The effect of three different compression garments on time to exhaustion, oxygen uptake and lactate concentration during high intensity exercise - Hagele, M.; Sperlich, B.; Zinner, C.; Wahl, P.; Mester, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Compression stockings have become common among endurance athletes not only in long lasting events (e.g. marathon) but also in short and middle distance running. Although their use is widespread during these intense exercises, few scientific research were executed observing their influence during these kinds of exercise. Furthermore the majority of these studies focus on wearing stockings, whereas no study has investigated the effect on performance and related physiological variables when increasing the amount of compressive area onto the body. The aim of the study was therefore to investigate the influence of three different compression garments (stockings, stockings + tight, whole body compression) on maximal endurance performance and performance influencing parameters. Methods: 14 male well-trained endurance athletes (age: 27,1 ± 4,8 yrs, height: 183,1 ± 7,6 cm, weight: 76,3 ± 7,6 kg, VO2peak: 63,7 ± 4,9 ml*kg*min-1) performed an incremental step test on a treadmill, to assess the velocity for the following four high intensity exercise bouts (HIB), which started four days after the initial testing. During HIB, all subjects randomly wore textile with different compressive surface: 1. regular non compressive running gear, 2. compression socks, 3. compression tights and 4. whole body compression (tight & top). During each of the high intensity exercise bouts time to exhaustion (TLim), lactate concentration (LAC) and oxygen uptake (VO2peak) was measured. Results: TLim was 310 ± 130, 280 ± 76, 296 ± 90 and 281 ± 91 seconds for the non compressive, sock, tight and whole body condition, which constitutes no statistically significant difference (p<0,05). Either not significant was LA, where values of 7,6± 2,88, 7,31 ± 2,29, 7,64 ± 2,46 and 7,12 ± 2,11 mmol*l-1 were measured. This is supported by VO2peak, which was 59,8 ± 13,6, 62,9 ± 7,3, 60,3 ± 8,9 and 61,1 ± 8,6 ml*kg-1*min-1 and not significant as well. Conclusion: For the first time the effects of increasing the amount of compressive surface vs non compression on maximal endurance capacity was evaluated. The results of this study revealed no beneficial effects neither on time to exhaustion (TLim) nor on performance affecting variables like VO2 or LAC when wearing compressive textile. Although, one has to consider that the data was detected during a high intense exercise bout. Scientific data concerning long distance events like Marathon or Ironman are yet to be undertaken, what disallows suggestions about the physiological and psychological effects of compression clothing during long lasting endurance events.